Stocker Steer Gains and Fly Numbers as Impacted by Burn Date and Type of Mineral on Tallgrass Native Range – Year 4 - Jaymelynn K. Farney; Harley Allen; Larissa Muniz (Kansas Agricultural Experiment Station Research Reports, 2023)
This study aims to evaluate effectiveness of two operational management systems for steer gains and fly control. The first strategy evaluated was pasture burn date of March (MAR) or April (APR). The second management strategy was free-choice mineral with spices (SPICE) or without spices (CON). Eight pastures (n = 281 steers; initial weight 566 lb) were used in a 2 × 2 factorial treatment structure. Steers were weighed individually, randomly assigned to treatment, and grazed for 89 days. Weekly, 33% of steers were photographed to count flies and evaluated for hair coat score. Steers that grazed pastures that were burned in March had a greater average daily gain than those grazing pastures that were burned in April and resulted in nearly 30 pounds more gain per calf during the grazing season. Steers that consumed the mineral that contained the spices/essential oils had a 0.10 pound per day advantage as compared to steers on control mineral. There was an interaction between pasture burn date and mineral type where steers gained the most on March burned pastures (with no difference in mineral type), had the second greatest gains on the April burned pastures with Spice mineral, and had the lowest gains on the April burned pastures with Control mineral. Weather plays a very important role in cattle performance following a complete pasture burn, and in a year with excessive spring moisture and extreme drought beginning in June, a March burn was the better management practice.
Keywords: essential oils; spices; growth; ectoparasite; steer gains; tallgrass